Consequences of Polish Army Restructure for socio-economic Development of Municipality Territory - Piotrowska-Trybull, Marzena (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The subject of consideration in this article is Conversion in the army and its consequences on socio-economic development on the territory in Poland and other countries. The article presents results of research carried out in chosen municipalities where military units were stationed.